Assessment of long-term changes in subvalvular aortic stenosis in patients following transcatheter aortic valve implantation - Vladlen V. Bazylev; Andrey B. Voevodin; Alexey S. Masyutin (КардиоСоматика)
BACKGROUND: The clinical course, pathophysiology, and therapeutic options for valvular and subvalvular (accompanied by hypertrophic cardiomyopathy, HCM) aortic stenosis are well known separately, but the rare combination of severe aortic stenosis (AS) and obstructive HCM presents great diagnostic and treatment challenges. The combination of these diseases during transcatheter aortic valve implantation (TAVI) is associated with significantly worse hospital outcomes, including cardiogenic shock, renal failure, and death. There is evidence that TAVI without prior treatment of left ventricular outflow tract obstruction leads to higher mortality due to exacerbation of subvalvular obstruction.